Patterns of Religious Identity Resistance in the Translation of Fiqhu al-Nisa’ from Arabic into Indonesian - Imama Nur Layliyah; Sajarwa Sajarwa (Universitas Islam Negeri Madura, 2025)
This study examines the pattern of religious identity resistance in the translation of Fiqhu al-Nisa’ from Arabic into Indonesian. Resistance in this context refers to the translator's strategy in maintaining religious terms without domestication or significant cultural adaptation, in order to maintain the integrity of meaning, sacred value, and Islamic identity in the translated text. The research method used is descriptive qualitative with a comparative approach between the source and target texts. Data in the form of religious terms were analyzed based on Al Ghamdi’s categories of religious identity, which include eschatology, moral and ethical criteria, religious artifacts, religious buildings, religious events, religious groups, religious figures or appeals, religious sites, special religious activities, supernatural beings, and enlightenment terms. The findings indicate that the strongest resistance emerges in the categories of specific religious activities and moral and ethical criteria. It is because terms within these categories are deeply rooted in Islamic epistemology and function as carriers of doctrinal authority. Such terms are difficult to substitute or domesticate without compromising their theological specificity and sacred function. Therefore, the translator consistently preserves these terms through transliteration or literal translation. This practice is not merely due to the absence of equivalent terms in Indonesian but rather represents a deliberate ideological choice to resist the secularization of religious language. These findings affirm that the translation of religious texts constitutes an ideological practice that plays a crucial role in maintaining Islamic identity and authority in the target text.